Pengaruh Lingkungan Kerja Fisik, Komunikasi, Dan Kepemimpinan Terhadap Kinerja Karyawan PT.BPR Merta Sedana Badung - Agastia, Ngakan Putu Agung (E-Jurnal Manajemen; Vol 3 No 1 (2014), 2014)
Normal 0 false false false EN-US JA X-NONE MicrosoftInternetExplorer4 Determine the effect of physical work environment , communication , and leadership to employee performance at PT . BPR Sedana Merta . Population as well as samples in this study were employees of PT . BPR Merta Sedana 66 people . The method used to process the data multiple linear regression analysis demgan -f test and t-test . The results of this study are : physical work environment variables , communication , and leadership significant effect on the performance of simultaneous partial and employees at PT . BPR Merta Sedana Badung . Analysis produces standardized beta coefficient value of 0.357 which communication variables which are variables that dominant influence on the performance of employees at PT . BPR Merta Sedana Badung . Keywords : physical work environment , communication , leadership , employee performance /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"MS Mincho"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}